Time dependent constitutive behavior and fracture/failure processes. proceedings of the 2010 Annual Conference on Experimental and Applied Mechanics - Proulx, Tom (Thomas William) (Conference Proceedings of the Society for Experimental Mechanics Series, 2011)
This the third volume of six from the Annual Conference of the Society for Experimental Mechanics, 2010, brings together 56 chapters on Time-Dependent Constitutive Fracture and Failure. It presents early findings from experimental and computational investigations on Time Dependent Materials including contributions on Thermal and Mechanical Characterization, Coupled Experimental and Computational Analysis of Fracture Path Selection, Procedures for Mixed Mode Fracture Testing of Bonded Beams, and Experimental Study of Voids in High Strength Aluminum Alloys.